Dvajset let postopka zunajtelesne oploditve in mnogoplodna nosečnost - Tomaževič, Tomaž (Zdravniški vestnik, 2003)
Background. Slovene data on iatrogenic multiple pregnancy after IVF/ICSI procedures are presented. The influence of elective transfer of two high-quality embryos on the incidence of iatrogenic multiple pregnancy were evaluated. Methods. Retrospective analysis of the Slovene IVF/ICSI data in theperiod 1983-2000. Results. In 17436 IVF/ICSI cycles 3068 pregnancies were achieved. Of the 2308 deliveries 369 (16%) were twins and 49 (2%) triplets. Of the 2827 newborns 738 newborns (26%) were twins and 148 (5%) triplets. With elective transfer of two high quality embryos in 1999 and 2000 in two of the three Slovene centres for assisted reproduction, the pregnancy rate per transfer increased (32%), triplet deliveries decreased to 2/492 deliveries (0.4%) (p<0.0000), and twin deliveries remained unchanged 111/492 deliveries (23%). Conclusions. After elective transfer of two high-quallity embryos and cryopreservation of surplus high-quality embryos in two of the three Slovene centres in the years 1999 and 2000, the problem of iatrogenic triple and higher rate multiple pregnancies has been successfully resolved, but the twin delivery rate still remains too high. Only by elective transfer of a single high-quality embryo the high multiple pregnancy rate after IVF/ICSI procedures could be avoided.
Keywords: Embryo transfer; Fertilization in vitro; ginekologija; human pregnancy; in vitro fertilization; Injiciranje semena, intracitoplazmično; neplodnost; nosečnost; Nosečnost, mnogoplodna; Oploditev in vitro; Pregnancy, multiple; Sperm injections, intracytoplasmic; Zarodek, prenos; zunajtelesna oploditev